Output and inflation in models of the business cycle with nominal rigidities: Some counterfactual evidence - Juan Páez-Farrell (Cardiff University, Cardiff Business School, 2006)
This paper examines the relationship between cyclical output and inflation in models commonly used for monetary policy analysis. This includes models that incorporate the New Keynesian, Fuhrer-Moore and backward-looking Phillips curves. The main finding is that these models imply a strong negative relationship between inflation and output, a result that is at odds with the data. The fact that New Keynesian models yield counterfactual implications is not new; the novelty of the paper lies in the fact that the finding extends to the other variants, such as the backward-looking Phillips Curve, which has been put forward as displaying superior dynamics.
Keywords: E20; E31; E32; E52; E61; 330; nominal rigidities; monetary policy; Phillips Curve; Output; Inflation; Correlation